A Performance Evaluation of Mehr Eghtesad Bank Branches Based on the Balanced Score Card (BSC) and Analytic Network Process (ANP) Combined Model - Allahyar Beigifiroozi (پژوهش‌های مدیریت عمومی, 2017)
Extended Abstract The Knowledge of the functional status of banks provides the ability to identify the strengths and weaknesses caused the Strategic management act in a more aggressive compared with competitors. In this regard, the present study aimed to evaluate the performance of Mehre Eghtesad’s branches in Sistan and Baloochestan province based on BSC approach and analytic network process (ANP) was done. For this purpose, four performance dimensions, including financial, customer, internal processes and learning and growth were considered. To assess the performance of the branches in terms of financial, internal processes and learning and growth, the actual data contained in the financial statements and documents in 92 were used. And to measure customer dimension a questionnaire based on 5 Likert designed and distributed among each branch separately. In addition to comparing the functional aspects of the BSC and branches in terms of performance, a questionnaire was designed with the scale of 9 by ANP, and distributed among managers, department heads and experts numbered 40. Data analysis by SPSS and Super Decision software showed Iranshahr branch with 0.092 factor won first place. And then Moalemand bazar branches and other branches were the next ranks.   Introduction As before, Sistan and Baloochestan Province Mehr Eghtesad Bank only adopts financial index to evaluate its branches’ performance and rate them. A branch with high attraction of resources, appropriate consumption norms, and lower outstanding debts will naturally be more successful. Financial instruments, though, cannot by themselves express customer-oriented policies and employees’ agility in doing their tasks—the facts which refer to a deficit. The present article, thus, is aimed at adoption of the Balanced Score Card (BSC) and Analytic Network Process (ANP) combined model in evaluating the performance of Sistan and Baloochestan Province Mehr Eghtesad Bank Branches in order to present an in-depth evaluation of branches’ performance and rate them by means of four financial, customer, learning and growth, and internal processes   Case study Performance of Mehr Eghtesad Bank Branches in Sistan and Baloochestan Province   Materials and Methods The present study is descriptive-analytic in its nature, and practical in its purpose. To collect required data and analyze information, library-based investigations, interviews, and questionnaires were employed. Statistical populations of this research include 40 Sistan and Baloochestan Province Mehr Eghtesad Bank managers, branch heads, and employees in order to identify and evaluate relative importance of performance-cantered criteria and sub-criteria. In addition to them, a number of 205 customers were selected to examine their allegiance to and satisfaction form their bank services and products. To select manager and experts, non-probability, purposive judgmental sampling method was adopted. This is taken when collection of technical and accurate data has vital implications, and other probabilistic designs are unable to provide such assistance. Although, due to the fact that we select our sample group from among available technicians, judgmental sampling method may confine generalizability of findings, it is the only method which can be used about the persons who have the information intended by us. In order to distribute questionnaires among our unlimited customers, random stratified sampling method was employed. Here, open and guided interviews based on standard questions were made with a number of bank managers and experts to identify BSC criteria and sub-criteria for evaluation of Mehr Eghtesad Bank branches.   Discussion and Results After analyzing the information by the software Super Decision for priorities and performance of Sistan and Baloochestan Province Mehr Eghtesad Bank branches. Conclusion According to the research findings, Iranshahr Branch has obtained the 1st rank at all BSC performance aspects: it is more profit-making, more customer-oriented, and with more motivated, skilled employees. It, moreover, accomplishes its internal processes with the least expenses incurred.